Physicochemical and microbial alterations in rumen liquor during Lantana camara toxicity in buffalo calves (Bubalus bubalis)* - Madial, R K; Randhawa, S N S (The Indian Journal of Animal Sciences, 2012)
Rumen liquor analysis of Lantalla camara intoxicated buffalo calves revealed complete absence of protozoal motility, concentration and idophillic activity with significant (P